2018
DOI: 10.1093/jas/sky008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between endo-parasite phenotypes and economically important traits in dairy and beef cattle1

Abstract: Parasitic diseases have economic consequences in cattle production systems. Although breeding for parasite resistance can complement current control practices to reduce the prevalence globally, there is little knowledge of the implications of such a strategy on other performance traits. Records on individual animal antibody responses to Fasciola hepatica, Ostertagia ostertagi, and Neospora caninum were available from cows in 68 dairy herds (study herds); national abattoir data on F. hepatica-damaged livers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 72 publications
2
12
0
Order By: Relevance
“…Despite the lack of widespread reranking for milk production and carcass traits in the present study, considerable reranking of sires was expected for the fertility traits across the different F. hepatica prevalence levels; nonetheless, the estimated genetic correlations were associated with large sampling variability attributable mainly to the low heritability of the fertility traits and also a paucity of data at the extremes. The presence of the G × E interaction for fertility traits in environments differing in F. hepatica prevalence was not unexpected given the known genetic association that exists between fertility traits and F. hepatica-phenotypes (Twomey et al, 2018). The larger extent of reranking for fertility traits in the present study suggests that sires that descended in rank as F. hepatica prevalence increased were not resilient to the environmental load of F. hepatica.…”
Section: Rerankingsupporting
confidence: 47%
See 1 more Smart Citation
“…Despite the lack of widespread reranking for milk production and carcass traits in the present study, considerable reranking of sires was expected for the fertility traits across the different F. hepatica prevalence levels; nonetheless, the estimated genetic correlations were associated with large sampling variability attributable mainly to the low heritability of the fertility traits and also a paucity of data at the extremes. The presence of the G × E interaction for fertility traits in environments differing in F. hepatica prevalence was not unexpected given the known genetic association that exists between fertility traits and F. hepatica-phenotypes (Twomey et al, 2018). The larger extent of reranking for fertility traits in the present study suggests that sires that descended in rank as F. hepatica prevalence increased were not resilient to the environmental load of F. hepatica.…”
Section: Rerankingsupporting
confidence: 47%
“…This conclusion is substantiated by a simulation described by Mulder et al (2006) who reported that maximum genetic gain can be achieved by using only 1 breeding program if genetic correlations between environments were >0.6. The minimal extent of reranking in the present study for milk production and carcass traits in environments differing in F. hepatica prevalence was somewhat expected as milk production and carcass traits are only weakly genetically (May et al, 2017;Twomey et al, 2018) and phenotypically (Mezo et al, 2011;Sanchez-Vazquez and Lewis, 2013) associated with phenotypes reflecting F. hepatica infection. Nonetheless, a noticeable weakening of the within-trait genetic correlations between milk productions traits in F. hepatica prevalence levels >0.8 and the rest of the F. hepatica prevalence levels, however, these were associated to larger standard errors.…”
Section: Rerankingmentioning
confidence: 61%
“…The SNP effect correlations between rFEC-GIN and rMY were negative for three of the five identified ROI, corresponding to the estimates from pedigree-based random regression models [15]. Twomey et al [20] detected genetic correlations close to zero between milk yield and antibodies for Ostertagia ostertagi , the most common GIN species in cattle. In our study, mostly negative SNP correlations were inferred between rMY and rFLC-DV.…”
Section: Discussionmentioning
confidence: 90%
“…In most cases, negative SNP effect correlations were observed between rFEC-FH and rFEC-GIN, implying that genomic selection on improved resistance to F. hepatica infections simultaneously increased the susceptibility to GIN. The pedigree-based genetic correlations ranged from − 0.10 to 0.17 between different GIN and liver fluke trait definitions [15, 20]. One explanation for the negative correlations on a genomic scale between rFEC-FH and rFEC-GIN and for the divergent marker associations as well as gene annotations might be due to the variations in immune response mechanisms for different endoparasite species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation